Economic Convergence in the Euro Area : Coming Together or Drifting Apart? - Franks, Jeffrey; Barkbu, Bergljot; Blavy, Rodolphe; Oman, William (Washington, D.C. : International Monetary Fund, 2018)
We examine economic convergence among euro area countries on multiple dimensions. While there was nominal convergence of inflation and interest rates, real convergence of per capita income levels has not occurred among the original euro area members since the advent of the common currency. Income convergence stagnated in the early years of the common currency and has reversed in the wake of the global economic crisis. New euro area members, in contrast, have seen real income convergence. Business cycles became more synchronized, but the amplitude of those cycles diverged. Financial cycles showed a similar pattern: sychronizing more over time, but with divergent amplitudes. Income convergence requires reforms boosting productivity growth in lagging countries, while cyclical and financial convergence can be enhanced by measures to improve national and euro area fiscal policies, together with steps to deepen the single market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet